Razmerje med hegemonijo in ideologijo v Gramscijevi politični teoriji - Hočevar, Marko (Teorija in praksa, 2018)
The article deals with the relationship between hegemony and ideology in the political theory of Antonio Gramsci who, by insisting on the distinction between these two concepts, introduced both complexity and multidimensionality into the study of the political. Departing from the questions of how a historical movement is formed and the unity of structure and superstructure (historical block) is consolidated, the authors argue that the relationship between hegemony and ideology can only be understood in the context of Gramsci's entire political theory. Insisting on the conceptual distinction between hegemony and ideology is crucial for political science if it wants to understand and explain politics and the political with an appropriate conceptual and methodological apparatus.
Keywords: Gramsci, Antonio Francesco; Hegemony; Ideologija; Ideology; Nadvlada; Political theories; Politične teorije